Right ventricular outflow tract function in chronic obstructive pulmonary disease - Geyik, B.; Tarakci, N.; Ozeke, O.; Ertan, C.; Gul, M.; Topaloglu, S.; Aras, D.; Demir, A.D.; Tufekcioglu, O.; Golbasi, Z.; Aydogdu, S. (Herz, 2015)
Background It is clinically important to evaluate the severity of right ventricular (RV) overload in patients with chronic obstructive pulmonary disease (COPD), which is often associated with changes in the structure and the function of the right ventricle. Noninvasive and reliable assessment of RV function would be an essential determinant of RV load and a clinically useful factor for assessing cardiovascular risk in COPD patients. Objective The aim of this study was to investigate the clinical application value of right ventricular outflow tract (RVOT) systolic function measured by transthoracic echocardiography in patients with COPD. Patients and methods We prospectively investigated COPD male patients and compared them with healthy controls. In addition to RV conventional echocardiographic parameters, RVOT size and fractional shortening (RVOT-FS) parameters were also assessed. Results Fifty-five COPD patients (all men; mean age, 62 ± 9 years) participated in the study, and were compared with a control group consisting of 21male, healthy, nonsmoking subjects with a mean age of 58 ± 11 years. The RVOT-FS was impaired in COPD patients than healthy controls (27.8 ± 15.5 vs. 57.5 ± 8.6, p < 0.001), and was correlated positively with tricuspid annular plane systolic excursion (TAPSE; r = 0.583, p < 0.001) and pulmonary acceleration time (r = 0.666, p < 0.001) and inversely with pulmonary artery systolic pressure (r = 0.605, p < 0.001) and functional capacity(r = − 0.589, p < 0.001). There was a statistically significant difference in RVOT-FS among the COPD subgroups with regard to New York Heart Association functional classification (p < 0.001). Conclusion The RVOT-FS is a noninvasive easily applicable measure of RV systolic function and is well correlated with functional capacity in COPD patients. Its combination with long-axis measurements via TAPSE and transtricuspid Doppler analysis may provide a comprehensive evaluation of the RV performance in COPD patients.